VIKOR-KERNEL METHOD AND ITS USING TO MAKE A MULTIPLE CRITERIA ALTERNATIVES COMPARISON - Ihor S. Romanchenko; Mykhailo М. Potomkin (Sučasnì Informacìjnì Tehnologìï u Sferì Bezpeki ta Oboroni)
The algorithm of method VIKOR intended for ranging of alternatives, and results of its analysis are given. It is shown that some shortcomings are inherent in known method VIKOR. It is caused by necessity of use of additional balancing factor, and also by indeterminate form of interpretation of gained results. It is noted that elimination of these shortcomings is connected with necessity of essential alteration of VIKOR method. However its basic idea about comparison of alternatives by two criteria may be used to create a new outranking method – the VIKOR-kernel method. This new method will be intended not for ranging of alternatives, but for formation of a core which will contain or one best alternative, or some incomparable alternatives which are the most perspective for the further analysis. For this new method settlement dependences, and also rules of comparison of alternatives which provide core formation are given. Possibility of practical use of the offered VIKOR-kernel method is demonstrated by two settlement instance. The results for these two settlement instance with using wellknown multiple criteria optimization methods are given in literature. Comparison of results of the calculations gained with use known and new methods, testifies that use of the VIKOR-kernel method in a combination with other methods allows to raise validity of developed recommendations or to find perspective alternatives which have not been revealed by other methods. These results allow to draw a conclusion that using of the offered VIKOR-kernel method can be perspective enough for multiple criteria optimization of complex objects.